2007
DOI: 10.1124/jpet.107.119560
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Seven Opioids in P-Glycoprotein-Competent Mice: Assessment of Unbound Brain EC50,uand Correlation of in Vitro, Preclinical, and Clinical Data

Abstract: This study was conducted to assess the utility of unbound brain EC 50 (EC 50,u ) as a measure of in vivo potency for centrally active drugs. Seven -opioid agonists (alfentanil, fentanyl, loperamide, methadone, meperidine, morphine, and sufentanil) were selected as model central nervous system drugs because they elicit a readily measurable central effect (antinociception) and their clinical pharmacokinetics/pharmacodynamics are well understood. Mice received an equipotent subcutaneous dose of one of the model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(107 citation statements)
references
References 18 publications
6
99
0
Order By: Relevance
“…For P-gp substrates, the unbound plasma concentration is expected to be higher than the unbound brain concentration Liu et al, 2008). This result has also been recently demonstrated by Kalvass et al (2007b). They showed that the unbound plasma EC 50 for antinociceptive activity in mice of loperamide, a P-gp substrate, was more than 50-fold of its in vitro K I , whereas its unbound brain EC 50 was similar to its K I .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…For P-gp substrates, the unbound plasma concentration is expected to be higher than the unbound brain concentration Liu et al, 2008). This result has also been recently demonstrated by Kalvass et al (2007b). They showed that the unbound plasma EC 50 for antinociceptive activity in mice of loperamide, a P-gp substrate, was more than 50-fold of its in vitro K I , whereas its unbound brain EC 50 was similar to its K I .…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, total brain concentration does not represent the drug concentration at the biophase. Although the scientific rationale for the free drug hypothesis is very strong, there are limited data in the literature to actually prove that the unbound brain concentration, not the total brain tissue concentration, determines CNS activity (Cox et al, 1998;Kalvass et al, 2007b;Watson et al, 2009). Because of the lack of extensive well documented data in the literature and the lack of understanding of novel drug targets in most drug discovery and development programs, sometimes it is debatable whether the unbound brain concentration or the total brain concentration determines in vivo activity.…”
mentioning
confidence: 99%
“…In contrast, the half-life of 6b-naltrexol in humans is much longer than that in mice (.11 hours;Yancey-Wrona et al, 2011). Similarly, the half-life of methadone in rodents is only 1-3 hours, approximating the clearance and analgesic time profile of morphine (Pacifici et al, 1994;Kalvass et al, 2007b), highlighting species differences in opioid PK. Therefore, the metabolic properties of 6b-naltrexol are suitable for sustained alleviation of the fetal dependence-inducing effects of the common opiates used for the management of adult addiction in the clinic, methadone and buprenorphine.…”
Section: Discussionmentioning
confidence: 93%
“…This analysis approach has been used previously to model the time course of whole brain-to-plasma ratios of several opiate drugs (Kalvass et al, 2007).…”
Section: Methodsmentioning
confidence: 99%